Efek Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Pengungkapan Corporate Social Responsibility Sebagai Variabel Mediasi pada Perusahaan Konstruksi yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016 - Robert Robert (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to analyze : The effect of profitability and firm size on CSR, the effect of CSR on firm value, and the effect of profitability and firm size on the firm value through CSR. Subject is the construction company listed in the Indonesia Stock Exchange (BEI) 2014-2016. The sampling technique that used purposive sampling techniques and obtained as many as 68 companies with a total of 204 observations. This study using non-participant observation method taken from annual report and financial statement of companies. The analysis technique used is two stage least square regression method. The results of this study are : Profitability doesn’t effect on CS. Firm Size proven significant positive effect on CSR. CSR proven negative and significant on firm value and CSR able to mediate effect of Profitability and firm size on the firm value.